Assessment of glucose homeostasis in young adult female β-thalassemia major patients (β-TM) with acquired hypogonadotropic hypogonadism (AHH) never treated with sex steroids compared to eugonadal β-TM patients with spontaneous menstrual cycles: OGTT in female β-thalassemia major patients with AHH - De Sanctis, Vincenzo; Daar, Shahina; Soliman, Ashraf T; Tzoulis, Ploutarchos; Di Maio, Salvatore; Kattamis, Christos (Acta Biomedica Atenei Parmensis, 2023)
Background: Acquired ypogonadotropic hypogonadism (AHH) is the most prevalent endocrine complication in thalassemia major (TM). Study design: Considering the detrimental effect of estrogen deficiency on glucose metabolism, the ICET-A Network promoted a retrospective study on the long-term effects of estrogen deficiency on glucose homeostasis in female β-TM patients with HH without hormonal replacement therapy (HRT). Patients and Methods: Seventeen β-TM patients with AHH (4 had arrested puberty; Tanners’ breast stage 2-3), never treated with sex steroids, and 11 eugonadal β-TM patients with spontaneous menstrual cycles at the time of referral were studied. A standard 3-h OGTT was performed in the morning, after an overnight fast. Six-point plasma glucose and insulin level determinations, indices of insulin secretion and sensitivity, early-phase insulin insulinogenic index (IGI), HOMA-IR and β-cell function (HOMA-β), oral disposition index (oDI), glucose and insulin areas under the OGTT curves were evaluated. Results: Abnormal glucose tolerance (AGT) or diabetes was observed in 15 (88.2%) of 17 patients with AHH and 6 (54.5%) of 11 patients with eumenorrhea. The difference between the two groups was statistically significant (P: 0.048). However, the group of eugonadal patients was younger compared to AHH patients (26.5 ± 4.8 years vs. 32.6 ± 6.2 years ; P: 0.010). Advanced age, severity of iron overload, splenectomy, increased ALT levels and reduced IGF-1 levels were the main clinical and laboratory risk factors for glucose dysregulation observed in β-TM with AHH compared to eugonadal β-TM patients with spontaneous menstrual cycles. Conclusion: These data further support the indication for an annual assessment of OGTT in patients with β-TM. We believe that a registry of subjects with hypogonadism is necessary for a better understanding of the long-term consequences of this condition and refining treatment options.